Memory of Power Transformed - Maleska, Kalina (MI-AN Publishing, 2018)
This essay is focused on the phenomenon of power. Special attention is paid to the past understanding, research and explanation of what power is, and how it has been understood throughout history. Traditionally, power has referred to authority, influence, control. The research of literary works, however, has led me to the realization that the notion of power is understood in different terms in literature in comparison to how it is explained in philosophy and the social sciences. In order to contribute to the broader understanding of power from a literary point of view, this essay examines many questions concerning this phenomenon, such as: how does the past understanding of power determine how it is accepted and interpreted in the present? How are the success of the present efforts and initiatives affected by the memory of power? The essay attempts to show that the memory of the notion of power is not and cannot be fixed and given once and for all. Therefore, the literary examples provided demonstrate how the definitions of power given in the past are transformed and transfigured by present literary works, which show how we may “forget” what we know about this phenomenon, and define it from a new perspective.